Mangrove Litterfall and Its Carbon Contribution: A Study on Coastal Carbon Reserves in Sungai Nibung Village, West Kalimantan - Sofiana, Mega Sari Juane; Safitri, Ikha; Mardianto, Tomi; Farhaby, Arthur Muhammad (Jurnal Kelautan Tropis, 2025)
Mangroves play an essential ecological roles, such as providing habitats for various organisms and contributing to reducing CO2 emissions from human activities. These emissions are one of the main causes of global warming and climate change. This study aims to analyze the litter production rate and carbon content of mangrove litter in Sungai Nibung Village, Kubu Raya Regency, West Kalimantan. Sampling of mangrove litter was conducted for 14 days using a 1x1 m2 litter trap with a mesh size of 0.2 cm. The litter traps have been placed in 9 stations. Litter samples were collected on the 7th and 14th days, including parts of mangroves (leaves, twigs, flowers, and fruits) that naturally fell. Result of the study showed the total litter production rate ranged from 4.95 to 30.07 tons/ha/year, and the findings reveal a clear hierarchy in litter production with the composition being leaves > twigs > propagules/fruits > flowers. Leaves litter production rate is notably high, followed by twigs which represent the second-largest portion, then fruits, and flowers. Meanwhile, the total carbon content varied across sampling station, accounting for 2.30–23.59 tons/ha/year. This research provides essential baseline data for Sungai Nibung Village and highlights the potential of mangroves as significant carbon sinks. The results can be utilized for ecosystem-based coastal management and mangrove restoration aligned with regional environmental policies.